2002
DOI: 10.2116/analsci.18.137
|View full text |Cite
|
Sign up to set email alerts
|

Design of a New Dodecyl Sulfate-Selective Electrode Based on Conductive Polyaniline

Abstract: A new, simple, sensitive, low cost and rapid potentiometric method for direct determination of ultra trace amounts of sodium dodecyl sulfate (SDS) with a new DS --selective electrode is reported. The electrode was prepared by electropolymerization of aniline in acidified DS -ion on the surface of a Pt electrode. The cyclic voltammetry (CV) was used for electropolymerization of polyaniline (PA) in the potential range of -200 to +1000 mV vs. Ag/AgCl. This sensor showed a Nernstian behavior (59.0 ± 2.3 mV/decade)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…A solid-state ISE for determination of dodecylsulfate (DS -) was prepared by Mousavi et al [123] . Vinokurov and Kankare [125] explained theoretically the potentiometric response of PANI to aniline based on the formation of charge-transfer complexes between aniline (donor) and the oxidized form of PANI (acceptor).…”
Section: CLmentioning
confidence: 99%
“…A solid-state ISE for determination of dodecylsulfate (DS -) was prepared by Mousavi et al [123] . Vinokurov and Kankare [125] explained theoretically the potentiometric response of PANI to aniline based on the formation of charge-transfer complexes between aniline (donor) and the oxidized form of PANI (acceptor).…”
Section: CLmentioning
confidence: 99%
“…The PVC commercial electrodes or other made with platinum [25] cannot adapt easily to a continuous flow system, given their configuration and construction. Only the supported PVC membrane electrodes of adequate configuration are useful for such systems [13].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the development of sensors selective for SDS has been carried out considering batch determination [22 ± 25], however, continuous determinations (i.e., by FIA) of amphiphilic molecules have received less attention in spite of their inherent relevant applications. Recently, Mousavi et al [25] reported a dodecyl sulfate-selective electrode based on conducting polyaniline. This sensor presents Nernstian behavior, a wide linear range and a very interesting detection limit for DS À (1.0 Â 10 À9 M), requiring platinum as the polyaniline membrane substrate and its useful lifetime is restricted to one month only, however, it has not been proven in a FIA system…”
Section: Introductionmentioning
confidence: 99%
“…Histamine [265], histidine [266], imidazole [267,268], ketamine [269], ascorbic acid [270], oxalate [271], triamterene [272], naphazoline [273], valproate [274], cystein [275], theophiline [276], sulfosalicylic acid [277], thiosalicylic acid [278], salicylate [279,280], ketoconazole [281], clotrimazole [282], cimetidine [283], diclofenac [284], atenolol [285], picrate [286], linear alkylbenzene sulfonate [287,288], sodium dodecylsulfate [289][290][291], dodecylbenzene sulfonate [292] aresepecies the sensors of which have been introduced by Iranian researchers.…”
Section: Selective Electrodes For Drugs and Organic Speciesmentioning
confidence: 99%
“…As it is seen from Table 3, these sensors were based on ionophores like different complexes of iron(III) [265], iron(II) [270], copper(II) [271], zirconyl(IV) [277], nickel(II) [279], tin(IV) [280], lead(II) [275], aluminum(III) [278] and manganese(III) [265], 2,4,6- ClO 4 -, SCN -PME/ CGE [279] triphenylthiopyrilium perchlorate [267], 4-methyl-2,6-diphenylthiopyrylium [268], ion-exchanger sites [269], tetraphenylborate ion [272], tetraphenylborate [273], conducting polypyrrole films [274], 2,6-bis(phenyl)-4(phenyl) 3H-thiopyran [276], phthalocyanine [278], ketoconazoletetraphenyl borate ion pair [281], phosphomolybdate [282], phospoho tungstate [283], hexadecylpyridinium bromide [284], tetrakis(p-chlorophenyl) borate [285], polypyrrole [287,290], and hyamine [288], polyaniline-dodecylsulfate [289], cetylpyridinium cation [291], polyaniline [292], which have different natures and hence different selection mechanisms.…”
Section: Selective Electrodes For Drugs and Organic Speciesmentioning
confidence: 99%